The efficacy of intermittent pneumatic compression and negative pressure therapy on muscle function, soreness and serum indices of muscle damage: a randomized controlled trial - Szczepan Wiecha; Martyna Jarocka; Paweł Wiśniowski; Maciej Cieśliński; Szymon Price; Bartłomiej Makaruk; Jadwiga Kotowska; Dorota Drabarek; Igor Cieśliński; Tomasz Sacewicz (BMC, 2021)
Abstract Background The study aimed to assess whether intermittent pneumatic compression (IPC) and intermittent negative pressure (INP) would attenuate the muscle damaging effects of eccentric exercise. Methods Forty-five healthy males were recruited. Immediately post, 24 and 48 h post eccentric exercise consisting of 100 drop jumps, volunteers randomly received 30-min sessions of intermittent pneumatic compression (IPC, n = 15) or intermittent negative pressure (INP, n = 15), or sham microcurrent (PT, n = 15). Creatine kinase (CK), lactate dehydrogenase (LDH), isokinetic muscle strength, soreness and active flexion of the knee joint were measured after every therapy session. Results No significant intergroup differences were observed in biochemical or functional measurements. However, there was an increase in muscle soreness (P < 0.05), CK and LDH activity (P < 0.05), and a reduction in muscle strength (P < 0.05) and range of active knee flexion (P < 0.05). Conclusions The prescription of IPC and INP did not attenuate the reduction of markers to muscle function or pain perception up to 48 h after muscle damaging exercise. Future research should focus on the potential impact of treatment frequency and duration on muscle recovery. Trial registration The study was retrospectively registered in the Australian New Zealand Clinical Trials Registry (ANZCTR); The trial registration number: ACTRN12621001294842; date of registration: 24/09/2021.